Perspektif Leverage, Capital Intensity, dan Manajemen Laba Terhadap Tax Aggressiveness - Yayang Eka Pratiwi; Rachmawati Meita Oktaviani (ITB AAS INDONESIA, 2021)
The research aims to analyze the factors that are affecting the tax aggressiveness. The research includes as a quantitative research by using a secondary data that obtained from the financial statement of the company. The population of the research is the entire manufacturing company listed in the Indonesian Stock Exchange during the year of 2016-2019. The collected sample is conducted by using a purposive sampling of company listed in the Indonesia Stock Exchange in 2016-2019, the financial statement in rupiahs, and manufacturing companies with a CETR of less than one. The sample has met the criteria of 32 companies in four years. The used data analysis techniques by panel data regression using EViews 10. The result shows that the Leverage and Earning Management has a positive impac in the tax aggressiveness, while the variables on capital intensity do not affect the tax aggressiveness.